2022
DOI: 10.2147/dddt.s363702
|View full text |Cite
|
Sign up to set email alerts
|

Influences of Bifid Triple Viable Capsules Plus Cetirizine on Gut Microbiota and Immune Function in Children with Eczema

Abstract: Objective Infantile eczema (IE), a common pediatric allergic skin disease caused by multiple inherent and external factors, is common in infants and young children, with skin lesions and itching as the main clinical manifestations. At present, its pathological mechanism has not been thoroughly clarified, but scholars believe that it is related to the joint action of various internal and external factors. This research aims to investigate the influences of bifid triple viable capsules plus cetirizi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…The incidence rate of eczema in infants is high, especially in infancy [6]. Although the pathogenesis of infantile eczema has not been fully elucidated, many reports have indicated that the occurrence of infantile eczema is often related to the immature development of the immune system, the imperfect development of the intestinal barrier, family genetics, environmental factors (drugs, smoking environment), and the baby's diet [7]. Recent studies have suggested that the development of the gut microbiota is decisive to the proper function of the guts and the development of the immune system [8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The incidence rate of eczema in infants is high, especially in infancy [6]. Although the pathogenesis of infantile eczema has not been fully elucidated, many reports have indicated that the occurrence of infantile eczema is often related to the immature development of the immune system, the imperfect development of the intestinal barrier, family genetics, environmental factors (drugs, smoking environment), and the baby's diet [7]. Recent studies have suggested that the development of the gut microbiota is decisive to the proper function of the guts and the development of the immune system [8].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the baby is routinely given a certain dose of Vit D (preventive dose 400 IU/d) until the age of two years [12]. Infantile eczema is often accompanied by immune dysfunction and dysbiosis of the intestinal florae [7]. Therefore, this study aimed to investigate if changing the dose of vitamin D can make the intestinal flora and immune function of eczema infants who usually adhere to Vit D 400 IU/d feeding return to normal levels.…”
Section: Introductionmentioning
confidence: 99%